Metric domains, holomorphic mappings and nonlinear semigroups - Simeon Reich; David Shoikhet (Abstract and Applied Analysis)
We study nonlinear semigroups of holomorphic mappings on certain domains in complex Banach spaces. We examine, in particular, their differentiability and their representations by exponential and other product formulas. In addition, we also construct holomorphic retractions onto the stationary point sets of such semigroups.